A newly recorded Rickettsia of the Torix group is a recent intruder and an endosymbiont in the whitefly Bemisia tabaci. (5th February 2020) - Wang, Hua‐Ling; Lei, Teng; Wang, Xiao‐Wei; Maruthi, M. N.; Zhu, Dan‐Tong; Cameron, Stephen L.; Rao, Qiong; Shan, Hong‐Wei; Colvin, John; Liu, Yin‐Quan; Liu, Shu‐Sheng
Summary: The bacterium Rickettsia is found widely in phytophagous insects and often exerts profound effects on the phenotype and fitness of its hosts. Here, we decrypt a new, independent, phylogenetically ancient Torix Rickettsia endosymbiont found constantly in a laboratory line of an economically important insect Asia II 7, a putative species of the Bemisia tabaci whitefly complex (Hemiptera: Aleyrodidae), and occasionally in field whitefly populations. This new Rickettsia distributes throughout the body of its whitefly host. Genetically, compared to Rickettsia_ bellii_MEAM1 found earlier in whiteflies, the new Rickettsia species has more gene families and pathways, which may be important factors in shaping specific symbiotic relationships. We propose the name ' Candidatus Rickettsia_Torix_ Bemisia_tabaci (RiTBt)' for this new endosymbiont associated with whiteflies. Comparative genomic analyses indicate that RiTBi may be a relatively recent intruder in whiteflies given its low abundance in the field and relatively larger genome compared to Rickettsia _bellii_MEAM1.